HELPING PROFESSIONS FOR SOCIAL PROGRESS: PERSPECTIVES OF THE GRADUATE STUDENTS - Pipere, Anita; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The paper aims to explore how future practitioners in helping professions grasp the wider societal problems and represent their professional practice in terms of social progress. The inquiry illustrates the perspectives of students by triangulation between their understanding of main societal issues in Latvia in the context of national planning documents (NPDs), social capital (SC), and expectations about their future work. Data of 34 first-year graduate students were collected using the open questionnaire and analyzed employing inductive and deductive thematic analysis. The largest group of societal issues contained the socio-psychological problems followed by economic challenges. Only half of the answers concerning SC were in tune with the theoretical conceptualization of this term. The students’ views on societal issues and SC did not align well with the NPDs. The mentioned socio-psychological problems contained the issues of relationship and value aspects of SC, omitting the social networks. One-third of answers in terms of professional expectations were related to the development of SC, other answers focused on the demands of external entities, and the students’ features. The views of graduate students can become an important signpost for the development of graduate programs in times of global interest in core competencies for helping professions.